Monocromos : de Malevich al presente. - Fabre, Gladys; Ho, Christopher K.; Rose, Barbara; Trione, Vincenzo (Madrid : MNCARS (Museo Nacional Centro de Arte Reina Sofia) Madrid, 2004)
Abakanowicz, Magdalena ; Albers, Josef ; Andre, Carl ; Arman ; Arp, Hans (Jean) ; Asensio, Juan ; Asins, Elena ; Bados, Angel ; Ballester, José Manuel ; Bell, Larry ; Bianchi, Domenico ; Bill, Max ; Bonalumi, Agostino ; Booker, Chakaia ; Burri, Alberto ; Byars, James Lee ; Casanova, Arturo ; Castellani, Enrico ; Chillida, Eduardo ; Chryssa ; Degottex, Jean ; Demarco, Hugo ; Devade, Marc ; Diaz, Gabriel ; van Doesburg, Theo ; Eversley, Frederick ; Fontana, Lucio ; Goeritz, Mathias ; Goode, Joe ; Hantaï, Simon ; Hentschläger, Kurt ; Hernandez Pijuan, Juan ; Honegger, Gottfried ; Irwin, Robert ; Judd, Donald ; Kapoor, Anish ; Kelly, Ellsworth ; Klein, Yves ; kline, martin ; Kobro, Katarzyna ; Kolibal, Stanislav ; Kusama Yayoi ; Kuwayama, Tadaaki ; Laib, Wolfgang ; Longobardi, Nino ; Mack, Heinz ; Malevich, Kasimir ; Manzoni, Piero ; Marden, Brice ; Marioni, Joseph ; Martin, Agnes ; Martin, Jason ; Matisse, Henri ; McCracken, John ; Meireles, Cildo ; Miro, Joan ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Monet, Claude ; Morellet, François ; Morris, Robert ; Moskowitz, Robert ; Naito, Rakuko ; Navarro, Miquel ; Newman, Barnett ; Nicholson, Ben ; Noël, Georges ; Noguchi, Isamu ; Noland, Kenneth ; O'Keeffe, Georgia ; Olitski, Jules ; Opalka, Roman ; Parc, Julio Le ; Peters, Ana ; Pietrosanti, Roberto ; Pousette-Dart, Richard ; Rauschenberg, Robert ; Reinhardt, Ad ; Richter, Gerhard ; Rodchenko, Alexander ; Rueda, Gerardo ; Ryman, Robert ; San José, Ángeles ; Schoonhoven, Jan ; Scully, Sean ; Shelton, Peter ; Sicilia, José Maria ; Solano, Susana ; Soto, Jesus Rafael ; Soulages, Pierre ; Stella, Frank ; Strzeminski, Wladyslaw ; Taeuber-Arp, Sophie ; Tàpies, Antoni ; Tinguely, Jean ; Tobey, Mark ; Torner, Gustavo ; Turrell, James ; Tutundjan, Leon ; etc.
Spaans
Monocromos : de Malevich al presente, MNCARS (Museo Nacional Centro de Arte Reina Sofia), Madrid, 2004-06-15. 2004-09-06
boek